Preparation of pendant group-functionalized amphiphilic diblock copolymers in the presence of a monomer activator and evaluation as temperature-responsive hydrogels - Lee, Hye Yun; Park, Ji Hoon; Ji, Yun Bae; Kwon, Doo Yeon; Lee, Bo Keun; Kim, Jae Ho; Park, Kinam; Kim, Moon Suk (Polymer, 2018)
Temperature-responsive hydrogels have been widely developed for biomedical applications. In this study, 4-benzyloxy-ε-caprolactone (CL-OBn) was synthesized and the subsequent ring opening polymerization (ROP) of ε-caprolactone (CL) and CL-OBn monomers was performed by using the hydroxyl group of methoxy polyethylene glycol (MPEG) in the presence of HCl·Et2O as a monomer activator. MPEG-b-poly (ε-caprolactone) (MC) with benzyl pendant groups (MC-OBn) was successfully obtained in almost quantitative yield and the segment ratios and molecular weights were close to the theoretical values. Deprotection of the benzyl pendant groups successfully provided MC with hydroxyl pendant groups (MC-OH). Suspensions of MC-OBn and MC-OH exhibited distinct sol-to-gel phase transitions as a function of the temperature. The sol-to-gel phase transition of the MC-OBn and MC-OH diblock copolymers depended on the type (benzyl or hydroxyl) and amount of pendant groups in the diblock copolymer structure. The pendant group on the MC-OBn and MC-OH diblock copolymers either stabilized and/or destabilized hydrophobic aggregation between the MC segments. The hydrophobic aggregation was confirmed by the detection of crystallinity in the MC-OBn and MC-OH diblock copolymer suspensions. In conclusion, MC-OBn and MC-OH diblock copolymers were successfully prepared and served as temperature-responsive hydrogels.
Keywords: Amphiphilic diblock copolymers; Biomedical applications; Crystallinities; Hydrophobic aggregations; Methoxypolyethylene glycol; Pendant groups; Poly (epsiloncaprolactone); Temperature-responsive hydrogels; Crystallinity; Monomer activator; Pendant group; Phase transition; Temperature-responsible hydrogels